A Case Report of High-Grade Endometrial Stromal Sarcoma: A Rare Cause of Abnormal Uterine Bleeding in a Young Woman - Nuntasiri Eamudomkarn; Yuwadee Itarat; Pilaiwan Kleebkaow; Chumnan Kietpeerakool (Case Reports in Obstetrics and Gynecology)
High-grade endometrial stromal sarcoma (HG-ESS) is a rare clinical entity, particularly among young women, and only few cases have been reported in the literature. Herein, we describe the case of a 21-year-old woman who presented with a four-month history of excessive bleeding per vagina. Endometrial curettage and cervical biopsy revealed a malignant round cell tumor suggestive of metastatic sarcoma of uterine origin. Computed tomography of the abdominopelvic region showed an enlarged uterus with diffused thickening throughout the entire endometrial cavity. Intraabdominal lymphadenopathy and ascites in the pelvic cavity were noted. The patient underwent total abdominal hysterectomy, bilateral salpingo-oophorectomy, resections of the enlarged pelvic nodes, omentectomy, and biopsy of the peritoneal nodules in the cul-de-sac. Histological examination revealed a tumor with a permeative growth pattern composed of uniformly high-grade round cells with brisk mitotic activity and extensive lymphovascular space invasion. Sections of the pelvic lymph nodes on both sides and the peritoneal nodule revealed multiple metastatic foci. Immunohistochemical studies showed positive diffuse staining for vimentin, CD 10, and cyclin D1. The pathological diagnosis was HG-ESS stage IIIC. The patient experienced rapid progression of the disease while receiving adjuvant treatment and succumbed eight months after the operation. HG-ESS is a rare cause of AUB in adolescents and young women but should be considered in the differential diagnosis.